The Security Right of an Execution Order on Tangible Property - Knežević, Marko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Enforcement law reforms have not bypassed the enforcement of monetary claims against tangible property. The security right of an execution order acquired by an attachment levy (ger. Pfändungspfandrecht), since the previous Law on Enforcement and Security, is now acquired only by registration, at the request of the executive creditor. The paper tries to give dogmatic contours to this new concept. Starting from the already completed theories in German and Austrian doctrine, it turns out that for the current Serbian concept the most appropriate is so-called mixed theory. At the same time, however, its deficits and erroneous evaluations of the legislator are shown.
Keywords: execution Procedure, security right of an execution order